Different soliton pulse order effects on the fiber communication systems performance evaluation - Mahmoud M. A. Eid; Abd El-Naser A. Mohammed; Ahmed Nabih Zaki Rashed (Institute of Advanced Engineering and Science, 2021)
The study outlined the soliton pulse order effects on the performance efficiency of the optical transceiver systems. The power after fiber is reported for various Soliton pulse order. Max optical signal power (SP) and min optical noise power (NP) are clarified versus time after optical fiber for various soliton pulse order. As well as the max electrical power amplitude against time period is demonstrated after electrical filter for various soliton pulse order. It is reported that the optical transceiver performance efficiency can be upgraded with the first soliton order pulse. The soliton technique is used for high speed communication transmission systems. Soliton technique is used to compensate the dispersion and balanced with nonlinear effects. The soliton order effects is then discussed to choose the suitable soliton order for high speed system performance efficiency. The soliton techniques can be used also for extended ultra high transmion distance with high data rates.